WebSphere Business Integration Server Foundation V5.1 for z/OS - Holl, Sabine (IBM redbooks., 2004)
This IBM Redbooks publication helps you install and configure WebSphere Business Integration Server Foundation V5.1 on zOS. We describe the new Programming Model Extensions, their functionality and our experience deploying applications which use these new functions. Chapter 1, "Introduction to WebSphere Business Integration Server Foundation V5.1 for z/OS" on page 1, presents an overview of the product and why to use it on z/OS . Part 1, "Setting up the environment" on page 21 describes setting up WebSphere Business Integration Server Foundation V5.1 for z/OS in two scenarios. Part 2, "Testing the applications" on page123, discusses deploying the applications developed for the book WebSphere Business Integration Server Foundation V5.1 Handbook, SG24-6318. Part 2 describes the z/OS-specific tasks to deploy these applications into our environment, and how the Programming Model Extensions take advantage of z/OS functionality, such as Workload Manager. Please note that the additional material referenced in the text is not available from IBM